Simulation of incipient transformer faults - Palmer-Buckle, P.; Butler, K.L.; Sarma, N.D.R.; Kopp, A. (Circuits and Systems; Proceedings: Midwest Symposium on Circuits and Systems, 1998)
This paper adapts a method of modeling internal winding faults of three-phase power transformers for single-phase distribution transformers. The model which is compatible with the alternative transients program, ATP, allows the simulation of turn-to-earth and turn-to-turn faults on either windings of a single-phase, two-winding, distribution transformer. Results of staged internal winding faults of a distribution transformer are compared with the simulation results to validate the model. The experimental results were found to be comparable to those of the simulation.